Peran Tokoh Agama Dalam Meningkatkan Partisipasi Politik di Pilkada 2018 di Desa Batung - Sari, Yel Parta; Masyhur, Masyhur; Fikri, Muhammad Sirajudin (Ampera: A Research Journal on Politics and Islamic Civilization, 2021)
Abstract Regional head elections cannot be separated from the political dynamics that occur in the village. In various regions, the use of identity politics is rampant as campaign material. Therefore, Bawaslu is collaborating with religious leaders to make several movements against the politicization of religion and the issue of identity politics in the 2018 Pilkada campaign. Because the explanation of religious leaders will be very important to cool the warm atmosphere of the 2018 Pilkada campaign. The same is the case with the regional head elections in Betung Village. namely by prioritizing a religious figure as someone who can provide a broad understanding of the 2018 Banyuasin Pilkada. This research was conducted using qualitative data types. The data source is done by using primary data obtained from field studies and secondary data obtained from literature studies which are then processed and analyzed qualitatively in order to obtain conclusions. Based on the results of research and data analysis, it can be concluded that religious leaders have a very important role in regional head elections in Betung Village. Keywords: religious leaders, regional heads